The Effect of Special Exercises using Marcie Wedge Device Associated with the Laser Therapy in Rehabilitation of Elbow Joint Injured for Women - Tahseen Abdulkarim Amin (Journal of Global Pharma Technology, 2016)
The importance of the research of reducing the duration of therapy and the importance of modern equipment used in the research, either in the therapy or in the exercises, the researcher used laser therapy, the latest method in the world, which provides therapy injury and infected return to practice daily work at a record speed, Marcy Wedge in the performance of strength exercises, flexibility and slow pace. The researcher also used the 200-EK3 electronic device to measure the muscle strength in Newton units. The problem of the research lies in the length of the therapy programs used in the rehabilitation centers, which are not in the interest of the infected, so the researcher considered reducing the duration of therapy through the use of modern and sophisticated equipment, And effort. The aim of the study was to prepare strength and flexibility exercises using the Marcy Wedge and Laser Therapy sessions in the rehabilitation of the injured elbow in women. Also, the impact of strength exercises and flexibility associated with laser therapy sessions in the rehabilitation of the injured elbow in women. The researchers also used the 200-EK3 electronic device to measure muscle strength in Newton units. The problem of the research lies in the length of the therapy programs used in the rehabilitation centers, which are not in the interest of the infected, so researchers considered reducing the duration of therapy through the use of modern and sophisticated devices, and effort. The aim of the study was to prepare strength and flexibility exercises using the Marcy Wedge and Laser therapy sessions in the rehabilitation of the injured elbow in women. Also, the impact of strength exercises and flexibility associated with laser therapy sessions in the rehabilitation of the injured elbow in women. The researchers used the experimental approach in the design of a single group and in the method of pretests and post measurement. The study was conducted on a sample of (20 patients) who were deliberately chosen from among the women who had a tennis injury. Their age ranged from 25-30 years. The sample was then subjected to laser therapy sessions and exercises to increase the strength and flexibility of the affected joint. The researchers concluded that the therapeutic laser had a positive effect on pain relief and the speed of wound healing. The strength and flexibility exercises using the Marcy wedge system increased the strength and flexibility of the injured joint. The researchers recommended the need to adopt laser in the therapy of various injuries for it to achieve good results and fast time.Keywords: Strength and flexibility exercises, Marcy Wedge and Laser.